An Insight Into Structure, Function, and Expression Analysis of 3-Hydroxy-3-Methylglutaryl-CoA Reductase of - Kamalakshi Devi; Lochana Patar; Mahendra K Modi; Priyabrata Sen (Bioinformatics and Biology Insights, 2017)
Citronella ( Cymbopogon winterianus ) is one of the richest sources of high-value isoprenoid aromatic compounds used as flavour, fragrance, and therapeutic elements. These isoprenoid compounds are synthesized by 2 independent pathways: mevalonate pathway and 2-C-methyl- d -erythritol-4-phosphate pathway. Evidence suggests that 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) is a rate-controlling enzyme for the synthesis of variety of isoprenoids. This study reports the isolation, characterization, and tissue-specific expression analysis of HMGR from citronella. The modelled HMGR is a class I type of HMGR enzyme with 3-domain architecture. The active site comprises a cofactor (nicotinamide adenine dinucleotide phosphate) and the substrate-binding motifs. The real-time and quantitative reverse transcription-polymerase chain reaction results revealed equal expression level in both leaf sheath and root tissue. The results from our study shall be a valuable resource for future molecular intervention to alter the metabolic flux towards improvement of key active ingredient in this important medicinal plant.